1972
DOI: 10.1002/hrm.3930110204
|View full text |Cite
|
Sign up to set email alerts
|

Adequate grievance channels: Overcoming the negative effects of work measurement on employee morale

Abstract: Organizations that are searching for improved efficiency by instituting programs like work measurement may find that their efforts are countered by a loss of employee morale that follows in the wake of the program. Concern for these two goals, efficiency and morale, is often phrased in terms of mutual excluiiveness. That is, there is a feeling that movement toward one goal inevitably results in a proportionate movement away from the other. This assumption of goal incompatibility underlies the frequently stated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The recent focus in productivity does not take into account an employee’s satisfaction at work (Jenaro, Flores, & Arias, 2007). Several researchers have looked at the relationship between performance measurement and employee attitudes (e.g., Böckerman & Ilmakunnas, 2012; Rodriguez, von Glahn, Rogers, & Safran, 2009a; Rodriguez, von Glahn, Elliott, Rogers, & Safran, 2009b; Sirota & Wolfson, 1972a; Sirota & Wolfson 1972b). Sirota and Wolfson (1972a) administered a survey to 1,200 employees and assessed for employee morale and work measurement.…”
Section: Therapist Performance Management and Productivity Standardsmentioning
confidence: 99%
See 4 more Smart Citations
“…The recent focus in productivity does not take into account an employee’s satisfaction at work (Jenaro, Flores, & Arias, 2007). Several researchers have looked at the relationship between performance measurement and employee attitudes (e.g., Böckerman & Ilmakunnas, 2012; Rodriguez, von Glahn, Rogers, & Safran, 2009a; Rodriguez, von Glahn, Elliott, Rogers, & Safran, 2009b; Sirota & Wolfson, 1972a; Sirota & Wolfson 1972b). Sirota and Wolfson (1972a) administered a survey to 1,200 employees and assessed for employee morale and work measurement.…”
Section: Therapist Performance Management and Productivity Standardsmentioning
confidence: 99%
“…Several researchers have looked at the relationship between performance measurement and employee attitudes (e.g., Böckerman & Ilmakunnas, 2012; Rodriguez, von Glahn, Rogers, & Safran, 2009a; Rodriguez, von Glahn, Elliott, Rogers, & Safran, 2009b; Sirota & Wolfson, 1972a; Sirota & Wolfson 1972b). Sirota and Wolfson (1972a) administered a survey to 1,200 employees and assessed for employee morale and work measurement. They found that there was a negative relationship between productivity requirements and employee morale (Sirota & Wolfson, 1972a).…”
Section: Therapist Performance Management and Productivity Standardsmentioning
confidence: 99%
See 3 more Smart Citations